Problem Solving on English Verbal Sentence Formation for University Students - Ekalestari, Susi; Suhendi, Andang; Purwarno, Purwarno (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2020)
This is a preliminary research on problem solving on English verbal sentence formation for university students. Specifically, the problem is on the usage of auxiliary verbs in making sentences. This problem is met up with a new paradigm (pattern) in which the pattern is mapped out with keywords. Keywords are purposed to ease the students in applying auxiliary verbs when they are making English sentences. The new pattern is tested by a test before and after the introduction of the new pattern and by interviewing ten students to know their opinion about the benefit of the new pattern. The result shows that there is a significant decrease of errors made by the students after the introduction of the new pattern. The decrease achieves 49%. Furthermore, the whole interviewees’ responses show that the new pattern really helps them in making English sentence properly.